Study of Macular Pigments in Glaucoma - Siah, We Fong (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2021)
The macula can be involved in the early stage of glaucoma, as evidenced by the presence of paracentral scotoma on visual field tests (Drance 1969) or thinning of the ganglion cell complex (GCC) layer on optical coherence tomography (OCT) scans (Hood et al. 2013). In the human retina, the ganglion cells are most densely located at the macula and about 50% are concentrated within 4.5 mm of the fovea (Curcio & Allen 1990). Macular pigment (MP), which is composed of the hydroxycarotenoids lutein (L), zeaxanthin (Z) and meso-zeaxanthin (meso-Z), is also known to be most densely concentrated around the fovea (Trieschmann et al. 2008). Both L and Z are solely of dietary origin, while meso-Z can be synthesised de novo from retinal L (Bone et al. 1993). Disability glare is a visual complaint that can be present during the early stage of age-related macular degeneration (AMD) (Scilley et al. 2002) and glaucoma (Nelson et al. 2003, Goldberg et al. 2009). The aetiology of glare disability in glaucoma is poorly understood and currently, little can be offered to the patient to alleviate this debilitating problem. Oral dietary MP supplementation has been shown to augment macular pigment optical density (MPOD) and improve visual function including glare in individuals with AMD (Weigert et al. 2011, Liu et al. 2015) and those without underlying ocular disease (Stringham & Hammond 2008, Loughman et al. 2012). Our earlier work had demonstrated that MP levels may be compromised in glaucoma (Igras et al. 2013). This provided a rationale for the exploration of MP in glaucoma in particular, (a) the study of the relationship between MP and glaucoma-related structural parameters and visual function respectively, and (b) to evaluate the effect of MP supplementation on glaucoma structure and function. The Macular Pigment & Glaucoma Trial (ISRCTN registry number: 56985060) was a placebo-controlled, double-masked study where subjects with a diagnosis of open angle glaucoma (OAG) were randomly assigned to either receive a daily oral MP supplement (10mg L, 2 mg Z & 10mg meso-Z) (Active group) or placebo for a period of 6 months. MPOD at 0.25?, 0.5? & 1? retinal eccentricity were measured using a customised heterochromatic flicker photometry technique at baseline and at the end of the trial. Glaucoma-related structural parameters were captured using RTVue Fourier-domain OCT. Standard automated perimetry (HVF) 24-2 & 10-2 patterns, mesopic contrast sensitivity with glare (mCSg), photo-stress recovery time (PRT), self-reported visual symptoms and dietary questionnaire were evaluated. A total of 88 subjects with OAG were recruited into the study. Of this, 83 completed the trial (Active group, n = 43; Placebo group, n = 40). A cross-sectional analysis of the baseline date showed that MPOD was peaked centrally at 0.25? of retinal eccentricity and declined at more peripheral eccentricities. Mean deviation (MD) of HVF 24-2 and 10-2 significantly correlates with MPOD at 0.25? and 0.5? of retinal eccentricities. Those with foveal-involved GCC loss (n = 52) had significantly lower MPOD at 0.25?, 0.5? & 1? of retinal eccentricities, greater glaucoma severity (lower glaucoma-related OCT parameters, worse HVF 24-2 & 10-2 MDs), worse low spatial f mCSg (at 1.5cpd & 3cpd) and a prolonged PRT in comparison to those without foveal involvement. Those who reported glare symptoms had a significantly lower MPOD including those with foveal involvement. Those with foveal field loss displayed lower MPOD, overall worse HVF 24-2 and 10-2 MD, and higher PRT. At follow-up, a significant increase in MPOD was observed at 0.5? of retinal eccentricity for those in the Active group with foveal-involved GCC loss. No effect on glaucoma-related OCT parameters and visual function were observed in the Active group at the end of the trial. In summary, MPOD was found to be reduced with worsening glaucoma severity especially when the fovea was involved. We showed a significant relationship between MP and HVF 10-2 MD, a measure of severity of central VF loss. Furthermore, the inter-relationships observed between MP and mCSg suggest that lower MPOD in the presence of global central field loss as a potential factor in the development of glare symptoms among glaucoma subjects. MPOD augmentation, albeit small, was observed following 6 months of oral dietary MP supplementation. Future studies with a longer duration of MP supplementation are required to better evaluate MPOD response and to investigate the effect on visual function.
APPROVED
Keywords: glaucoma; macula; macular pigments; macular pigment optical density; ganglion cell complex; visual field; contrast sensitivity; oral supplementation